(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Mass media have traditionally utilized advertising as a strategy to connect with customerswho are diverse in their preferences. Conversely, cross-cultural advertising research refers to thesubfield of advertising studies that investigates problems or topics connected to ads in different culturalcontexts. Most advertising that describes cultures do so via a lens of celebration, as such celebrationserves as a universal symbol of and tribute to the culture. In order to better understand the culturalportrayal that has been conveyed via the ad material, the research has taken audio-video ads fromdifferent businesses from both foreign and Indian viewpoints. Commercials for the same companiesfrom various cultural viewpoints were shown in focus groups to gauge participants’ reactions to suchdepictions of cultural diversity. People’s conceptions of culture converged on a trinity of belief,transmission from generation to generation, and behavior. Participants in focus groups also providesuggestions like the depiction is less realistic, less practical, missing essence, etc., which, ifincluded, might help close the gap between the audience’s expectation and the portrayal of the messagevia advertising.